আগামী দিনের বাংলাদেশ - ইসলাম, নজরুল, ১৯৫৭- (ঢাকা : প্রথমা প্রকাশন, 2012)
Articles on the socio-economic condition and policies of Bangladesh; includes some articles on the present political condition of Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Economics; Bangladesh -- Economic conditions; Bangladesh -- Economic policy; Bangladesh -- Social conditions; Bangladesh -- Social policy; Bangladesh -- Politics and government -- 1971-